Diffracted Beams from Metasurfaces: High Chiral Detectivity by Photothermal Deflection Technique. Issue 21 (19th August 2021) - Leahu, Grigore; Petronijevic, Emilija; Li Voti, Roberto; Belardini, Alessandro; Cesca, Tiziana; Mattei, Giovanni; Sibilia, Concita
Abstract: Measurements of difference in optical interactions between circularly polarized excitations of opposite handedness (circular dichroism) are highly important for both natural and artificial chiral structures. Here the photothermal deflection technique is proposed as a method to detect the optical chirality of a metasurface, analyzing the diffracted beams by the metasurface itself. Two metasurfaces are investigated, based on Au and Ag. The samples are fabricated by nanosphere lithography, with a tilted deposition of thin metal layer, which produces symmetry‐breaking. The unit cell periodicity of these metasurfaces allows for multiple order diffraction in the 450–520 nm range, which encompasses the emission lines of an Ar laser. The metasurfaces are placed on a mirror and excited by an Ar pump beam at different orientations, laser wavelengths, and circular polarization degree; the probe beam scans the absorption of the diffraction orders back‐reflected from the underlying mirror. In this way, the chiral investigation is simplified by placing the scanning of absorption‐induced thermal effect into the metasurface plane, thus avoiding the transmission/reflection measurements of a specific order, which are done by angular placement of detector. Theoretical and numerical approaches are further developed to reconstruct both thermal and optical behavior of the chirality at the nanoscale. Abstract : The photothermal deflection technique applied on the diffracted beams produced by a metasurface is an extremely sensitive method to detect intrinsic and extrinsic optical chirality of the sample. The diffracted orders contain background‐free information on the symmetries of the sample. The samples are fabricated by nanosphere lithography, with a tilted deposition of thin metal layer, which produces symmetry breaking.